Blended Learning Berbasis Aplikasi Kreatif: Membangun Literasi Digital dan Tanggung Jawab Teknologi Siswa SD - Yuniarsih, Krisma; Prastowo, Andi (Inovasi: Jurnal Diklat Keagamaan, 2025)
The rapid development of digital technology demands a learning strategy that can equip students with digital literacy and responsibility in using technology from an early age. This study aims to describe the strategy of developing digital literacy and technological responsibility through blended learning based on creative applications in grade 4 elementary school. The research used a qualitative approach with a case study method. Data were collected through in-depth interviews with a grade 4 teacher at a private primary school in Sleman Regency and observation of the Indonesian language learning process in grade 4. Data were analyzed using integrated thematic analysis with a focus on coding and grouping patterns of meaning from qualitative data. The results show that digital literacy development strategies are implemented through the integration of creative applications such as Canva, Capcut, Ibis Paint and Keynote in presentation tasks, animations and collaborative projects. Teachers adopted a student-centered learning approach by giving students freedom to explore technology (FGDs, project-based learning), while controlling the use of non-educative apps through the iPad locking feature. Technological responsibility is developed through collaboration with parents in limiting the use of gadgets at home as well as instilling an attitude of responsibility through the habituation of using iPads since grade 4. The combination of blended learning, creative applications, technology control, and collaboration of stakeholders (teachers-parents) is the key in building digital literacy while directing students to the positive use of technology. The implication of this research can be a reference for educators in designing learning strategies that are adaptive to technological developments, especially at the elementary school.